Dutch Consumers' Willingness to Pay for Broiler Welfare - Mulder, Machiel; Zomer, Sigourney (Journal of applied animal welfare science, 2017)
This article analyzes Dutch consumers' willingness to pay (WTP) for the welfare of broiler chickens and the consequences for nonhuman animal welfare policies. Using data from a discrete-choice experiment and a random parameter logit model, this study showed that consumers particularly value opportunities for outdoor access and the method used for anesthesia before slaughter. The WTP was also positively related to the number of consumers buying the same product, indicating that they experience the public-good dilemma. Moreover, the WTP was higher if consumers knew that animal welfare practices were subject to public or collective supervision. Women, people with more education, those with higher income, and nonreligious people had relatively high WTP values. For 87.5% of the respondents, the WTP exceeded the price difference between a broiler with a higher level of animal welfare and a regular chicken. The findings suggest that the Dutch market for broiler chickens can be improved by raising consumer confidence in the labeling system.